In-situ hot forging directed energy deposition-arc of CuAl8 alloy - Duarte, Valdemar R. (2022)
Funding Information: Authors acknowledge the Portuguese Fundação para a Ciência e a Tecnologia ( FCT - MCTES ) for its financial support via the project UID/EMS/00667/2019 (UNIDEMI). VD acknowledges Portuguese Fundação para a Ciência e a Tecnologia ( FCT - MCTES ) for funding the PhD grant SFRH/BD/139454/2018 . TAR acknowledges Portuguese Fundação para a Ciência e a Tecnologia ( FCT - MCTES ) for funding the PhD grant SFRH/BD/144202/2019 . Funding of CENIMAT/i3N by national funds through the Portuguese Fundação para a Ciência e a Tecnologia, I.P., within the scope of Multiannual Financing of R&D Units , reference UIDB/50025/2020–2023 is also acknowledge. This activity has received funding from the European Institute of Innovation and Technology (EIT) Raw Materials through the project Smart WAAM: Microstructural Engineering and Integrated Non-Destructive Testing. This body of the European Union receives support from the European Union's Horizon 2020 research and innovation programme. Parts of this research were carried out at PETRA III at DESY, a member of the Helmholtz Association. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020 . This project has received funding from the EU-H2020 research and innovation programme under grant agreement No 654360 having benefitted from the access provided by PETRA III at DESY in Hamburg, Germany within the framework of the NFFA-Europe Transnational Access Activity. The authors acknowledge support by OCAS NV and GUARENTEED via Joachim Antonissen. Funding Information: Authors acknowledge the Portuguese Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/EMS/00667/2019 (UNIDEMI). VD acknowledges Portuguese Fundação para a Ciência e a Tecnologia (FCT - MCTES) for funding the PhD grant SFRH/BD/139454/2018. TAR acknowledges Portuguese Fundação para a Ciência e a Tecnologia (FCT - MCTES) for funding the PhD grant SFRH/BD/144202/2019. Funding of CENIMAT/i3N by national funds through the Portuguese Fundação para a Ciência e a Tecnologia, I.P. within the scope of Multiannual Financing of R&D Units, reference UIDB/50025/2020–2023 is also acknowledge. This activity has received funding from the European Institute of Innovation and Technology (EIT) Raw Materials through the project Smart WAAM: Microstructural Engineering and Integrated Non-Destructive Testing. This body of the European Union receives support from the European Union's Horizon 2020 research and innovation programme. Parts of this research were carried out at PETRA III at DESY, a member of the Helmholtz Association. The research leading to this result has been supported by the project CALIPSOplus under the Grant Agreement 730872 from the EU Framework Programme for Research and Innovation HORIZON 2020. This project has received funding from the EU-H2020 research and innovation programme under grant agreement No 654360 having benefitted from the access provided by PETRA III at DESY in Hamburg, Germany within the framework of the NFFA-Europe Transnational Access Activity. The authors acknowledge support by OCAS NV and GUARENTEED via Joachim Antonissen. Remark: The supplementary material is temporarily available in the Drive folder here: https://drive.google.com/drive/folders/1SFFlhJlmL5p3IkQis8cB6UVWva3wozGi?usp=sharing. Publisher Copyright: © 2022 Elsevier B.V.